The Role of The General Procurement Plan Information System (SiRUP) in The Budget Implementation at The West Java Provincial Government - Darmawan, Ivan; Deliarnoor, Nandang Alamsah; Yuningsih, Neneng Yani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
Procurement of government goods and services is one of the most crucial parts of the government process. Presidential Regulation Number 12 of 2021 on the Procurement of Government Goods and Services reflects the government's commitment to enhancing the transparency and accountability of procurement processes. A key component of this initiative is the implementation of the General Procurement Plan Information System (SiRUP). This paper examines how SiRUP has contributed to the procurement of goods and services within the West Java Provincial Government. The method used in writing this article is a qualitative method with documentation studies. Data was obtained from secondary sources from the Bureau of Goods and Services Procurement of the West Java Provincial Secretariat. The findings of this study indicate that, despite the implementation of the SiRUP application, the procurement process within the West Java Provincial Government has not yet been fully optimized in practice. Improvements are needed, particularly in terms of human resources related to competency, as well as in the optimization of the system itself.